2016
DOI: 10.4336/2016.pfb.36.86.920
|View full text |Cite
|
Sign up to set email alerts
|

Divergência genética entre progênies de polinização aberta de Pinus caribaea var. hondurensis a partir de caracteres quantitativos

Abstract: Este trabalho foi realizado com o objetivo de estimar a divergência genética entre progênies de Pinus caribaea var. hondurensis, por meio de caracteres quantitativos. O experimento foi instalado em delineamento látice 10 x 10, triplo, com 100 tratamentos (96 progênies oriundas de polinização aberta de um pomar clonal da espécie e quatro testemunhas). Foram avaliados os caracteres: diâmetro a 1,30 m do solo, altura total de planta, volume cilíndrico, produção de resina total e resina por área de painel. Utilizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
3
0
4
Order By: Relevance
“…La información sobre la divergencia de un individuo candidato contribuye a la planeación futura y utilización eficiente de los recursos genéticos para potencializar y maximizar el crecimiento y rendimiento en la selección (Santos et al, 2016). La distancia máxima observada entre las progenies del área 1 fue de D 2 = 47,74 entre las progenies 17 y 15 y la mínima fue de D 2 = 2,13 entre las progenies 25 y 27.…”
Section: Resultados Y Discusiónunclassified
See 2 more Smart Citations
“…La información sobre la divergencia de un individuo candidato contribuye a la planeación futura y utilización eficiente de los recursos genéticos para potencializar y maximizar el crecimiento y rendimiento en la selección (Santos et al, 2016). La distancia máxima observada entre las progenies del área 1 fue de D 2 = 47,74 entre las progenies 17 y 15 y la mínima fue de D 2 = 2,13 entre las progenies 25 y 27.…”
Section: Resultados Y Discusiónunclassified
“…Nikles y Griffin (1992) relatan que la supremacía híbrida puede suceder a partir de la heterosis "per se", epistaxis o complementariedad de caracteres (efecto aditivo). Todos esos efectos podrán ocurrir entre individuos de grupos divergentes (Santos et al, 2016). TABLA 4.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Intra-specific crossing between divergent genotypes leads to increased long-term population general genetic variability and, consequently, to increased ability to respond to selective pressure (RIUS and DARLING, 2014). The more divergent the parents, the greater the possibility of having variability in the generated segregating population and the greater the possibility of reorganizing the alleles based on new favorable combinations (MANFIO et al, 2012;SANTOS et al, 2016). Another important factor lies on the fact that depression caused by inbreeding can be removed by breeding after one generation (JOHNSON et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…At first glance, discarding the analysis of volume in estimating genetic distance would be indicated; however, the impact of discarding volume, or even DBH, must be weighed accordingly, given that it is one of the main traits used in selection. Santos et al (2016) found contradictory results for Pinus caribaea var. hondurensis in terms of quantitative traits, where volume was the trait that contributed the highest percentage for genetic divergence (98%), followed by DBH (1.51%) and height (0.26%).…”
Section: Figurementioning
confidence: 99%